2019
DOI: 10.1021/acs.jpclett.9b01827
|View full text |Cite
|
Sign up to set email alerts
|

Superior Thermoelectric Performance of Ordered Double Transition Metal MXenes: Cr2TiC2T2 (T = −OH or −F)

Abstract: Using SCAN-rVV10+U, we show Cr2TiC2 and Cr2TiC2T2 (T = −F and −OH) MXenes are moderate band gap semiconductors mostly in the antiferromagnetic state. All investigated MXene structures show large Seebeck coefficients (>400 μV/K), especially Cr2TiC2 (>800 μV/K) and Cr2TiC2F2 (>700 μV/K). The hole relaxation time of p-type Cr2TiC2(OH)2 is found to be ∼8 ps, ensuring its superior electron transport properties in comparison to other investigated MXenes. It is also discovered that the surface functionalization could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 69 publications
0
38
0
Order By: Relevance
“…[ 56 ] It is worth noting that Ti 2 CO 2 , Zr 2 CO 2 , Hf 2 CO 2 , Sc 2 CO 2 , Sc 2 C(OH) 2 , Cr 2 C(OH) 2 , Cr 2 CF 2 , and Sc 2 CF 2 are considered to be semiconductors and non‐magnetic among MXenes. [ 57 ] The magnetic properties of MXenes include ferromagnetic(such as Cr 2 C [ 58 ] )and antiferromagnetic (such as Ti 3 C 2 , Cr 2 TiC 2 F 2 [ 59 ] ). [ 60 ] Similar to the optical and electrical properties, the magnetic properties of MXenes are also affected by many factors such as the composition of “M” and surface termination.…”
Section: Structures and Propertiesmentioning
confidence: 99%
“…[ 56 ] It is worth noting that Ti 2 CO 2 , Zr 2 CO 2 , Hf 2 CO 2 , Sc 2 CO 2 , Sc 2 C(OH) 2 , Cr 2 C(OH) 2 , Cr 2 CF 2 , and Sc 2 CF 2 are considered to be semiconductors and non‐magnetic among MXenes. [ 57 ] The magnetic properties of MXenes include ferromagnetic(such as Cr 2 C [ 58 ] )and antiferromagnetic (such as Ti 3 C 2 , Cr 2 TiC 2 F 2 [ 59 ] ). [ 60 ] Similar to the optical and electrical properties, the magnetic properties of MXenes are also affected by many factors such as the composition of “M” and surface termination.…”
Section: Structures and Propertiesmentioning
confidence: 99%
“…; n = 1, 2, 3; X = C or N; and T represents terminal groups, like OH, O, F, Cl, etc. The variety of terminal groups enables it to own great hydrophilicity and compatibility with many solvents. , Previous research studies proved that MXenes have a much lower diffusion barrier for ions with larger diameters, such as Na + and K + , with real benefits to fast charging/discharging processes for battery systems except Li-ion batteries. Its interlamellar space is open for ions to intercalate. , Moreover, MXene is metallic, with good electrical conductivity and mechanical flexibility, so it can serve as a promising candidate in numerous applications, such as alkali-ion battery systems, supercapacitation, , sensing, , H 2 storage, , catalysis, , etc. Apart from the first-reported Ti 3 C 2 T x , many other Mxenes have been successfully prepared and reported over the years, such as Ti 2 CT x , Ti 2 NT x , V 2 CT x , Mo 2 TiC 2 T x , V 4 C 3 T x , Nb 4 C 3 T x , Ta 4 C 3 T x , Ti 3 CNT x , Cr 2 TiC 2 T x , Zr 3 C 2 T x , Hf 3 C 2 T x , etc. Besides, plenty of MXene-based composite materials have been developed and utilized in various fields. When used in energy storage systems, including all kinds of batteries and supercapacitors, MXenes, as well as its composites, show extremely remarkable electrochemical performance, even though exploitation of more high-performance MXene materials and their study is far from enough.…”
Section: Introductionmentioning
confidence: 99%
“…Such an unprecedented progress in PSCs is mainly associated with the unique physicochemical properties of HPMs, including large light absorption coefficients, defect tolerance, , tunable band gap, and diversity in crystal structure. Moreover, it was found that HPMs exhibit ultralow thermal conductivity and high carrier mobility, which promise them as potential alternatives to the conventional thermoelectric materials (TMs). …”
Section: Introductionmentioning
confidence: 99%